2009
DOI: 10.1053/j.gastro.2009.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Bacteria Induce Colonic PepT1 Expression: An Implication in Host Defense Response

Abstract: Background & Aims-Expression of the di/tripeptide transporter PepT1 has been observed in the colon under inflammatory conditions, however, the inducing factors and underlying mechanisms remain unknown. Here, we address the effects of pathogenic bacteria on colonic PepT1 expression together with its functional consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Pathogenic bacteria (Nguyen et al, 2009) and lipopolysaccharides (Shu et al, 2002), the major components of the outer layer of Gram-negative bacteria, can also affect the expression of SLC15A1, which can transport bacterial peptides. Our trial was not designed to assess the impact of thymol on gastrointestinal microbiota because its antibacterial properties are well known, and thus we cannot speculate here on possible variations on the gastric bacteria profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic bacteria (Nguyen et al, 2009) and lipopolysaccharides (Shu et al, 2002), the major components of the outer layer of Gram-negative bacteria, can also affect the expression of SLC15A1, which can transport bacterial peptides. Our trial was not designed to assess the impact of thymol on gastrointestinal microbiota because its antibacterial properties are well known, and thus we cannot speculate here on possible variations on the gastric bacteria profile.…”
Section: Discussionmentioning
confidence: 99%
“…Our trial was not designed to assess the impact of thymol on gastrointestinal microbiota because its antibacterial properties are well known, and thus we cannot speculate here on possible variations on the gastric bacteria profile. Nevertheless, it is worth mentioning that transgenic mice overexpressing SLC15A1 and infected with Citrobacter rodentium had reduced colonic colonization by this microbe, compared with that observed in infected wild-type mice Effect of thymol on gene expression in pig stomach (Nguyen et al, 2009). Intriguingly, in a previous in vivo trial, we found that Citrobacter freundii, a microbe closely related to C. rodentium, was increased in the intestinal content of pigs fed thymol compared with that observed in control pigs (Jankzyk et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The apical activity of SERT is decreased following tEPEC infection of fully differentiated Caco-2 cells in a T3SS-dependent manner, but its expression at the brush border is unaffected (622). Intimate attachment of tEPEC to fully differentiated HT29-Cl.19A cells is followed by increased hPet1 expression and activity by activation of the transcription factor Cdx2 (623). Deletion of the escN, espA, espB, and espD genes, which encode parts of T3SS, and the gene encoding BFP revealed that both early and intimate tEPEC attachment are needed for the EPEC inhibitory effect on the apical sodium-dependent bile acid transporter to occur in fully differentiated Caco-2 cells (624).…”
Section: Structural and Functional Injuriesmentioning
confidence: 96%
“…For infecting WT and CD98 Tg mice with C. rodentium, food and drinking water were replaced with 20% sucrose containing C. rodentium (3.3 ϫ 10 7 CFU/ml) in distilled water overnight as previously described (36). Control groups were given normal drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…Colonic tissues were cultured in RPMI 1640 medium (Cellgro, Manassas, VA) with FBS as described previously (36). Briefly, 5-to 10-mm colon tissues of WT and CD98 Tg mice were placed on sterile foam squares in 6-well culture plates with the mucosal surface facing upwards.…”
Section: Methodsmentioning
confidence: 99%